1996
DOI: 10.1038/bjc.1996.338
|View full text |Cite
|
Sign up to set email alerts
|

A new human breast cancer cell line, KPL-3C, secretes parathyroid hormone-related protein and produces tumours associated with microcalcifications in nude mice

Abstract: Summary Parathyroid hormone-related protein (PTHrP) is the main cause of humoral hypercalcaemia of malignancy (HHM). We recently established a new human breast cancer cell line, designated KPL-3C, from the malignant effusion of a breast cancer patient with HHM. Morphological, cytogenetic and immunohistochemical analyses indicated that the cell line is derived from human breast cancer. The KPL-3C cells stably secrete immunoreactive PTHrP measured by a two-site immunoradiometric assay, possess both oestrogen and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…It has also been suggested that PTHrP may play a role in the development of osteolytic metastasis. In addition, our previous study suggested that PTHrP might play a role in the deposition of microcalcifications in breast cancer tissues (Kurebayashi et al, 1996). Other researchers have suggested certain roles of PTHrP as autocrine and paracrine growth factors in breast cancer cells .…”
Section: Reproducibility Of the Experimental Resultsmentioning
confidence: 82%
See 4 more Smart Citations
“…It has also been suggested that PTHrP may play a role in the development of osteolytic metastasis. In addition, our previous study suggested that PTHrP might play a role in the deposition of microcalcifications in breast cancer tissues (Kurebayashi et al, 1996). Other researchers have suggested certain roles of PTHrP as autocrine and paracrine growth factors in breast cancer cells .…”
Section: Reproducibility Of the Experimental Resultsmentioning
confidence: 82%
“…Recently, we established a novel human breast cancer cell line, KPL-3C, derived from a patient with humoral hypercalcaemia, and preliminary characterization revealed that this cell line possesses both ER and PgR and stably secretes a detectable amount of immunoreactive PTHrP into the culture medium. A glucocorticoid, progestin and vitamin D analogue significantly inhibited PTHrP secretion from KPL-3C cells in a dose-dependent manner (Kurebayashi et al, 1996). This background prompted us to investigate the effects of oestrogen and antioestrogens on PTHrP secretion in this cell line.…”
Section: Reproducibility Of the Experimental Resultsmentioning
confidence: 99%
See 3 more Smart Citations